The Hinterland Urbanised?. (July 2016) - Brenner, Neil
Abstract : What defines the urban? And can the non‐urban necessarily always be classified as rural?Neil Brenner, Director of the Urban Theory Lab at Harvard University Graduate School of Design, reflects on the lack of an overarching theory to describe these realms, and argues that what we call the countryside or the hinterland has become key to the process of capitalist urbanisation.